1997
DOI: 10.1021/bi9702703
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Calmodulin and a Functional Myosin Light Chain Kinase in the Activated Complex:  A Neutron Scattering Study

Abstract: Calmodulin (CaM) is the major intracellular receptor for Ca2+ and is responsible for the Ca2+-dependent regulation of a wide variety of cellular processes via interactions with a diverse array of target enzymes. Our current view of the structural basis for CaM enzyme activation is based on biophysical studies of CaM complexed with small peptides that model CaM-binding domains. A major concern with interpreting data from these structures in terms of target enzyme activation mechanisms is that the larger enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 33 publications
10
63
0
Order By: Relevance
“…A nominal resolution of the data is 1.2 nm, and details of the tertiary structure can obviously not be validated experimentally at this level of resolution, which is why we restricted ourselves to rigid body modeling. Solution scattering is rather sensitive to rigid body movements of structural domains and has successfully been used to model the quaternary structure of proteins (15)(16)(17). The use of rigid body modeling is justified by a high sequence homology between monomeric ␣B-crystallin and MjHSP16.5.…”
Section: Discussionmentioning
confidence: 99%
“…A nominal resolution of the data is 1.2 nm, and details of the tertiary structure can obviously not be validated experimentally at this level of resolution, which is why we restricted ourselves to rigid body modeling. Solution scattering is rather sensitive to rigid body movements of structural domains and has successfully been used to model the quaternary structure of proteins (15)(16)(17). The use of rigid body modeling is justified by a high sequence homology between monomeric ␣B-crystallin and MjHSP16.5.…”
Section: Discussionmentioning
confidence: 99%
“…This can occur rapidly: Ca 2ϩ ⅐CaM activates myosin light chain kinase at about the same rate as the two proteins associate (10 7 M Ϫ1 s Ϫ1 ) (42). A recent neutron diffraction study provides evidence that CaM indeed activates myosin light chain kinase by "inducing a significant movement of the kinase's CaM binding and autoinhibitory sequences away from the surface of the catalytic core" (50).…”
Section: Discussionmentioning
confidence: 99%
“…We designed the experiments so that initially, most of the peptide was bound to vesicles, and after mixing with Ca 2ϩ ⅐CaM, most of the peptide was bound to Ca 2ϩ -calmodulin. Control experiments showed that the relaxation time for MARCKS-(151-175) transfer from the membrane to CaM ( CaM ) was independent of both lipid concentration (for example, 50 (open symbols) labeled on the first and ninth residues of the peptide, respectively. We obtain the association rate constant for a peptide binding to a vesicle by multiplying the slope by ; if ϭ 4 ϫ 10 5 , k on Ϸ 3 ϫ 10 11 M Ϫ1 s Ϫ1 for LUV 600 (Table I).…”
Section: Calmodulin-induced Dissociation Of Marcks-(151-175) Frommentioning
confidence: 99%
“…Far more detailed models can be constructed when highresolution structures of individual domains or subunits composing the complex are available. Assuming that the tertiary structure of the domains is largely preserved upon the complex formation, rigid-body modelling can be used to build the macromolecular complexes (Ashton et al, 1997;Krueger et al, 1997;Svergun, Aldag et al, 1998). Thus, for an assembly of two subunits, the complex is constructed by varying six positional parameters describing the relative position and orientation of the second subunit with respect to the ®rst one.…”
Section: Introductionmentioning
confidence: 99%